CHARACTERISTICS OF THE CLINICAL COURSE OF COVID-19 INFECTION IN PREGNANT WOMEN - Mehrinoz O. Komilova; Shahnoza A. Zufarova; Azada S. Yuldasheva; Xabibaxon N. Negmatshaeva (Central Asian Journal of Medicine, 2024)
Different manifestations of symptoms and complications of coronavirus infection in pregnant women depend on the gestational period of pregnancy, women’s age, concomitant diseases and several other factors. Studying the clinical condition of COVID-19 in pregnant women will help to prevent side effects of the disease and develop preventive measures. The purpose of the study: to study the clinical features of the coronavirus in pregnant women. Conclusion: COVID-19 presents with stronger symptoms in pregnant women compared to women in other contingents, and the risk of transitioning to severe forms of the disease is relatively high in pregnant women. Conclusion: The development of complications of viral infection in pregnant women infected with the coronavirus is more frequent than in healthy women, and the analysis of the clinical course of COVID-19 in pregnant women provides an opportunity to take measures to prevent risks depending on the trimesters of pregnancy.